APLIKASI PUPUK ORGANIK CAIR KEONG MAS DAN PENAMBAHAN MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TERUNG - Sanjaya, Lucky; Sri Lestari, Rina (Journal TECHNO, 2024)
The purpose of research was to examine the effect of gold snail liquid organic fertilizer and organic planting media on eggplant growth and yield. The research is a field experiment prepared with RAKL. The first factor in the gold snail liquid organic fertilizer is 40 ml/L, 80 ml/L, and 120 ml/L. The second factor is the addition of planting media namely 20 kg/plot sawdust, 20 kg/plot cocopeat, and 20 kg/plot husk charcoal. Data were analyzed using ANOVA 5% level and further tested using DMRT 5% level and orthogonal contrast test. The results showed that there was an interaction between the treatment of gold snail liquid organic fertilizer concentration and organic growing media. The best combination in the treatment of 120 ml/L gold snail liquid organic fertilizer concentration with 20 kg husk charcoal planting media/plot against the stem diameter parameter of 35 days after planting and the best combination in the treatment of 80 ml/L gold snail liquid organic fertilizer concentration with sawdust planting media 20 kg/plot against the fruit weight parameter per hectare. The addition of cocopeat planting media of 20 kg/plot shows a heavier fruit weight value per fruit compared to the addition of husk charcoal planting media 20 kg/plot.